In situ neutron diffraction observations of Ti-TiB composites. (September 2019) - Singh, Harshpreet; Hayat, Muhammad; He, Zhen; Peterson, Vanessa K.; Das, Raj; Cao, Peng
Abstract: This paper characterizes and evaluates TiB/Ti composites during thermal treatment using in situ neutron diffraction. The composites were developed using a conventional press and sinter technique. Pure titanium (Ti) was chosen as the matrix, and different concentrations of TiB2 were used as the boron source for the in situ development of the TiB phase. The conversion of phases from TiB2 (2–10 wt.%) to TiB during heating and cooling in the Ti matrix was studied for the first time using in situ neutron diffraction. No metastable phases were observed during heat-treating of the samples. Microstructural evolution and tensile properties of these composites were also evaluated with the highest tensile strength recorded of 684.95 MPa for the sample containing 5 wt.% TiB2 .